A Life Cycle Assessment of Energy-saving and Carbon Reduction Potential ——Empirical research on a Road Reconstruction Project in China - Wang Ke (E3S Web of Conferences, 2024)
A life cycle standardized assessment module of energy-saving and carbon reduction is established based on the current road cost management software. The assessment module combines the domestic road material consumption quota and the main LCA database CLCD in China. Quantitative energy-saving and carbon reduction benefits of material and technical alternative measures could be calculated autocratically. Empirical project data shows that reducing concrete, reducing mixing temperature and reusing material of the old road are essential measures. It is possible to reduce carbon by 22-28% and save energy by 45-50%.